PENGARUH LAYANAN INFORMASI KARIER BIMBINGAN DAN KONSELING TERHADAP KEMATANGAN KARIER SISWA SEKOLAH MENENGAH KEJURUAN - Darmawan, Iwan; Mudhar, Mudhar (Penerbit Lafadz Jaya, 2026)
Career maturity is a crucial indicator of the success of vocational education, particularly in vocational high schools (SMK), which are designed to prepare students for employment and further education. This study aims to empirically examine the effect of guidance and counseling career information services on students’ career maturity. The study is motivated by the phenomenon that many vocational students still experience career confusion, lack clear career planning, and have difficulty making realistic career decisions. This research employed a quantitative approach using a survey method with a causal-comparative design. The population consisted of 250 twelfth-grade students of SMK Negeri 53 Jakarta, with a sample of 152 students selected through proportional random sampling. Data were collected using validated and reliable Likert-scale questionnaires measuring career information services and career maturity. Data analysis was conducted using simple linear regression after meeting normality and linearity assumptions. The results indicate that career information services have a positive and significant effect on students’ career maturity, with a significance value of 0.000 (p < 0.05) and a coefficient of determination of 0.457. These findings suggest that career information services contribute 45.7% to students’ career maturity. Therefore, well-structured and continuous career information services play a strategic role in enhancing vocational students’ career maturity.